Antiemetic doses of dexamethasone and their effects on immune cell populations and plasma mediators of inflammation resolution in healthy volunteers. (December 2018) - Barden, Anne; Phillips, Michael; Hill, Lisa M.; Fletcher, Evelyn M.; Mas, Emilie; Loh, P.S.; French, Martyn A.; Ho, Kwok M.; Mori, Trevor A.; Corcoran, Tomás B.
Highlights: Dexamethasone is an antiemetic used during surgery but its effects on glucose, immune function and specialised lipid mediators of inflammation resolution (SPM) are unknown. Plasma glucose, leukocytes and SPM were measured at 0, 4 h, 24 h and 1 week after a single dose of dexamethasone (0, 2, 4, or 8 mg) in healthy volunteers. Dexamethasone increased neutrophils and decreased monocyte and lymphocytes after 4 h, had no effect on glucose and reduced the SPM 17R-RvD1. Further studies in surgical patients are necessary if these changes affect acute infection risk in the post-operative period. Abstract: Introduction: The synthetic glucocorticoid dexamethasone is a commonly administered antiemetic. It has immunosuppressive effects and may alter postoperative blood glucose concentrations. Dexamethasone can effect key enzymes involved in inflammation resolution that is an active process driven by specialised lipid mediators of inflammation resolution (SPM). The purpose of this study in healthy volunteers was to examine whether dexamethasone effects cell populations and synthesis of SPM that are critical for the resolution of inflammation. Methods: Thirty-two healthy volunteers were randomly allocated to receive saline (Control) or dexamethasone 2 mg, 4 mg or 8 mg intravenously. Venous blood samples were collected at baseline before administration of treatment, and at 4 h, 24 h and one-week post-treatment. At each time point, measurements included blood glucose and macrophage migration inhibition factor (MMIF), full blood count including lymphocyte subsets, monocytes, neutrophils, eosinophils and basophils by flow cytometry, and plasma SPM using liquid chromatography tandem mass spectrometry. The effect of dexamethasone dose and time on all measures was analysed using linear mixed models. Results: There was a dose-dependent increase in neutrophil count after dexamethasone that persisted for 24 h. In contrast, there was a dose-dependent reduction in counts of monocytes, lymphocytes, basophils and eosinophils 4 h after dexamethasone, followed by a rebound increase in cell counts at 24 h. Seven days after administration of dexamethasone, all cell counts were similar to baseline levels. MMIF concentration, glucose and natural killer cell counts were not significantly affected by dexamethasone. There was a significant gender effect on plasma SPM such that levels of 17-HDHA, RvD1, 17R-RvD1 and RvE2 in females were on average 14%–50% lower than males. In a linear mixed model that adjusted for neutrophil count, there was a significant interaction between the dose of dexamethasone and time, on plasma 17R-RvD1 such that plasma 17R-RvD1 fell in a dose-dependent manner until 4 h after administration of dexamethasone. There were no significant effects of dexamethasone on the other plasma SPM (18-HEPE, RvE2, 17-HDHA, RvD1, RvD2 and 14-HDHA) measured. Discussion: This is the first study in healthy volunteers to demonstrate that commonly employed antiemetic doses of dexamethasone affect immune cell populations and plasma levels of 17R-RvD1 an SPM with anti-nociceptive properties. If similar changes occur in surgical patients, then this may have implications for acute infection risk in the post-operative period.